ILLEGAL MINING AND THE IMPACT ON TAX COLLECTION 2023: CASE OF PERU - Canales Baldárrago, Nataly (2024)
Objective: It seeks to analyze how tax collection is affected by illegal mining, with the purpose of the economic recovery of Peru in 2023. Method: The study adopted a quantitative method, with explanatory analysis and the design is non-experimental to examine the effects of tax collection with illegal mining in Peru period 2023; based on data from authorized SUNAT sources. Results: An effective association is observed, since the total collection of the mining tax amounted to S/. 7,181.9 million during the six months of 2023, decreasing by 54% compared to the same period in 2022. The mining industry of Peru contributes to the state through the payment of income taxes (IR), third category and special mining taxes, mining royalties, new mining royalties and others. Likewise, at an aggregate level, 1.77 million TMF of copper were produced in the January-August 2023 period, an increase of 18.1% compared to the production of the 2022 period. Conclusion: In summary, according to the results between the years 2022 and 2023 in the variables studied, an inverse relationship is observed between these two years, since the total collection of the mining tax amounted to S/ 7,181.9 million during the first six months of the year 2023, decreasing from 54% compared to the same period in 2022.As it is an area that has a certain influence from tax revenues, it is crucial to strengthen it to revitalize the country’s economy.